THE POTENTIAL OF THE ECOLOGICAL HOTEL IN KOH CHANG - Nonthalug , Kerkkrai; Na Thalang, Chawalee (Academic Journal of Thailand National Sports University, 2020)
The research “The Potential of The Ecological Hotel in Koh Chang” aimed to: 1) study the attitude and the knowledge on the ecological hotel of the hotel management and hotel staff in Koh Chang, 2) survey the assessment criteria of the ecological hotel, ) analyze the potential of the ecological hotel in Koh Chang. This study was conducted in a qualitative research method. The structured interview was conducted to 20 hotel managers and 20 hotel staffs with the content analysis as the qualitative study. The interview data indicated 1) The positive attitude and the knowledge were found in the ecological hotel of the hotel management and hotel staff in Koh Chang. 2) The assessment criteria of the ecological hotel were the environmental management, the human resource, the staff participation and the hotel management. 3) There were two environmental management challenges in Koh Chang, firstly the waste management, the garbage in the sea and lack of the properly waste separation, and secondly, there was not enough fresh water during summer in the high-season for tourism in Koh Chang. There were only the community water supply system and the underground water supply system in Koh Chang, but not enough in 4-5 star hotels. They need to buy fresh water to supply for the hotel business. 4) The analysis for the potential of the ecological hotel in Koh Chang based on the criteria of the “Green Hotel” , the” Green Leaf Hotel” and the concept of “7 Green”, displayed that the 2-3 star hotels were more successful to manage the ecological hotel while the 4-5 star hotels faced the challenge of waste management and fresh water management. In the human resource management, the small hotels had less headcount with the closer line of management. The type of hotel management for mostly 2-3 star hotels was the own-management by the hotel owner.